Performance and reliability evaluation of Sacramento demonstration novel ICPC solar collectors - Daosukho, Jirachote "Pong", author; Duff, William S., advisor; Troxell, Wade O., advisor; Burns, Patrick J., committee member; Breidt, F. Jay, committee member (Colorado State University. Libraries, 2012)
This dissertation focuses on the reliability and degradation of the novel integral compound parabolic concentrator (ICPC) evacuated solar collector over a 13 year period. The study investigates failure modes of the collectors and analyzes the effects of those failures on performance. An instantaneous efficiency model was used to calculate performance and efficiencies from the measurements. An animated graphical ray tracing simulation tool was developed to investigate the optical performance of the ICPC for the vertical and horizontal absorber fin orientations. The animated graphical ray tracing allows the user to visualize the propagation of rays through the ICPC optics. The ray tracing analysis also showed that the horizontal fin ICPC's performance was more robust to degradation of the reflective surface. Thermal losses were also a part of the performance calculations. The two main degradation mechanisms are reflectivity degradation due to air leakage and fluid leakage into the vacuum enclosure and loss of vacuum due to leaks through cracks. Reflectivity degradation causes a reduction of optical performance and the loss of vacuum causes a reduction in thermal performance.
Keywords: evacuated solar collector; reliability; performance; ICPC